2020
DOI: 10.1038/s41533-020-0167-1
|View full text |Cite
|
Sign up to set email alerts
|

Are COPD self-management mobile applications effective? A systematic review and meta-analysis

Abstract: The burden of chronic obstructive pulmonary disease (COPD) to patients and health services is steadily increasing. Selfmanagement supported by mobile device applications could improve outcomes for people with COPD. Our aim was to synthesize evidence on the effectiveness of mobile health applications compared with usual care. A systematic review was conducted to identify randomized controlled trials. Outcomes of interest included exacerbations, physical function, and Quality of Life (QoL). Where possible, outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 40 publications
2
52
0
1
Order By: Relevance
“…Mobile apps are increasingly being used to provide patients with health and self-management interventions, for example, for remote monitoring of patients’ health status [ 15 - 17 ], self-report of symptoms or health status [ 16 - 18 ], education [ 16 , 19 ], and digital support or feedback [ 15 , 17 , 18 ]. This is often combined with feedback from a health care professional or automated via the app [ 17 - 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile apps are increasingly being used to provide patients with health and self-management interventions, for example, for remote monitoring of patients’ health status [ 15 - 17 ], self-report of symptoms or health status [ 16 - 18 ], education [ 16 , 19 ], and digital support or feedback [ 15 , 17 , 18 ]. This is often combined with feedback from a health care professional or automated via the app [ 17 - 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews have showed that mobile device applications are effective for the self-management of COPD over usual care although there is insufficient evidence to date due to marked variation in methodology and reporting of outcome measures. 15,16 Therefore, further clinical validation remains essential to use mHealth in improving COPD care.…”
Section: Discussionmentioning
confidence: 99%
“…However, the value of monitoring physiological parameters to predict exacerbations 15 and also the effectiveness of mobile health applications compared with usual care are controversial. 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, recently we have seen the emergence of new programme formats that aim to improve access and uptake, including tele-rehabilitation and other home-based models. However, the evidence base for remotely delivered rehabilitation is not secure particularly in older patients with COPD [ 6 ]. Patient experience with remotely delivered healthcare is variable and will only be relevant for those who can access and engage with the technology [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%